Pemanfaatan Media Sosial Instagram Untuk Promosi Kampung Pancasila - Vivitri Endah Andriani; Mira Adita Widianti; Muhammad Iqbal Aulia (Jurnal Informasi Pengabdian Masyarakat, 2024)
The limited knowledge of the village community regarding social media Instagram as a medium for promoting Pancasila Village, Cikadu Village means that they are less able to introduce Pancasila Village optimally. Through Community Service activities, it is hoped that we can contribute to the use of Instagram social media to the local community. The aim of this activity is to provide education to the public on how to use Instagram social media to introduce and promote Pancasila Village and the potential that exists in Cikadu Village, so that it is hoped that the wider community can become more familiar and aware of the existence of Pancasila Village and its various potentials in Cikadu Village. Apart from that, this activity is expected to provide education regarding digital media literacy.